Ամուսնալուծության ռիսկերի հաղթահարումը իբրև ընտանիքի պահպանման գրավական - Մուրադյան, Արմինե (Զանգակ հրատ.)
В данной статье обсуждается и исследуется семья как социально-психологический предмет, обсуждаются семейные проблемы, в частности семейные конфликты, кризисы, разводы, факторы риска, из за которых семья разлогается, а также анализируются те механизмы, с помошью которых семейные пары смогли бы преодолеть тяжолую фазу развода. This article adresses and briefly analyses the family as a subject of social and psychological research, in particular the current relations between family and society, functions of family, its place and role in the present system are studied, family relantionships, divorced, divorced risks, family crizisises and confliqts. We have also tried to analyse the role social and psychological peculiarities of family and machinery of its relationship with society.
Keywords: Հոգեբանություն